Analisis Pengaruh Transfer Pemerintah Pusat terhadap Upaya Pemungutan Pajak Kabupaten/Kota di Indonesia - Nikijuluw, Ruth (UI Scholars Hub, 2012)
The main objective of this research is to get analytical results about the impact of intergovernmental transfers on the municipalities tax effort over the period of 2005-2008. This research uses regression approach method to calculate tax effort index and panel regression method to address the impact of central government transfer. Empirical evidence supports that generally intergovernmental transfers in kind of dana perimbangan has a positive relation with local tax effort. Meanwhile using the component of dana perimbangan, an increase in the untied grants (block grants), Dana Alokasi Umum (DAU) and Dana Bagi Hasil (DBH), significantly pushes the growth of local tax effort.